Antibacterial Activity of Borassus flabellifer Vinegar-Graphene Quantum Dots Against Gram-Positive and Gram-Negative Bacteria - Noypha, Amnuay; Porrawatkul, Paweena; Teppaya, Nongyao; Rattanaburi, Parintip; Chanthai, Saksit; Nuengmatcha, Prawit (Asian Journal of Chemistry, 2021)
Borassus flabellifer vinegar–graphene quantum dots (BFV-GQDs) were successfully synthesized using a pyrolysis method with Borassus flabellifer vinegar (BFV) as the precursor. All the samples were characterized using ultraviolet-visible spectrophotometry (UV-Vis), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). The antibacterial activities of BFV-GQDs against strains of Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) were determined using the agar well diffusion method for preliminary screening, while minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined using the broth macro-dilution method. The zones of inhibition were compared with those of citric acid–graphene quantum dots (CA-GQDs). It was observed that the synthesized BFV-GQDs demonstrated excellent antibacterial activity against Staphylococcus aureus (82.3%) and good antibacterial activity against Escherichia coli (73.3%). The MIC of BFV-GQDs against E. coli was 6.25 mg/mL and S. aureus was 12.5 mg/mL, whereas the MBC of BFV-GQDs against E. coli was 12.5 mg/mL and S. aureus was 25.0 mg/mL.